IMPLEMENTASI MODERASI BERAGAMA PADA MASYARAKAT MULTIKULTURAL DI MAN I JEMBRANA BALI - Anggraeni, Dewi; Salwa, Ahda Febzia; Safitri, Nanda Amalia; Fakhizati, Uzmatul; Noviana, Dewi (Universitas Pendidikan Indonesia, 2024)
AbstractThe existence of Islamic educational institutions in a predominantly Hindu society is both a challenge and an opportunity in implementing the values of religious moderation. The purpose of this study is to explore the implementation of religious moderation, especially in multicultural societies such as Bali through Islamic educational institutions. Through a qualitative approach, as well as descriptive analysis of MAN 1 Jembran as the research locus, the data collection technique uses open interviews, observation, and documentation. The data that has been collected is then analyzed through data presentation, development analysis (generalization), synthesis, and conclusion drawing. The results showed that the implementation of religious moderation in MAN 1 Jembrana was carried out by understanding the context of religious moderation in a multicultural society, integrating religious moderation through the curriculum by emphasizing ukhwah wathoniyah and ukhwah basyariah, religious moderation became a shared spirit through school culture with the motto MANJADDAWAJADA which was manifested in various concrete actions such as the formation of GANTARA and various extracurricular activities. This research also confirms that Balinese Hindus as the majority are very tolerant of Muslims in Bali.Keywords: Religious Moderation, Multicultural, Educational Institutions, Islamic educational institutions, MAN 1 JembranaAbstrakKeberadaan lembaga pendidikan Islam di tengah masyarakat yang mayoritas beragama Hindu menjadi tantangan sekaligus peluang dalam menerapkan nilai-nilai moderasi beragama. Tujuan penelitian ini untuk mengeksplorasi implementasi moderasi beragama khususnya pada masyarakat multikultural seperti Bali melalui lembaga pendidikan Islam. Melalui pendekatan kualitatif, serta analisis deskriptif terhadap MAN 1 Jembran sebagai lokus penelitian.Teknik pengumpulan data menggunakan wawancara terbuka, observasi, dan dokumentasi Data-data yang telah dikumpulkan kemudian dianalisis yang dituangkan melalui penyajian data, analisis pengembangan (generalisasi), sintesis, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi moderasi beragama di MAN 1 Jembrana dilakukan dengan pemahaman konteks moderasi beragama di tengah masyarakat multikultural, integrasi moderasi beragama melalui kurikulum dengan menekankan ukhwah wathoniyah dan ukhwah basyariah, moderasi beragama menjadi spirit bersama melalui budaya sekolah dengan moto MANJADDAWAJADA yang diwujdukan dalam berbagai aksi nyata seperti pembentukan GANTARA dan berbagai kegiatan ekstrakulikuler. Penelitian ini sekaligus menegaskan bahwa masyarakat Bali yang beragama Hindu sebagai mayoritas sangat toleran terhadap pemeluk agama Islam di Bali. Kata kunci : Moderasi Beragama, Multikultural, Lembaga Pendidikan, Lembaga Pendidikan Islam, MAN 1 Jembrana